1974
DOI: 10.1515/znc-1974-7-813
|View full text |Cite
|
Sign up to set email alerts
|

Über den Abbau von Chalkonen und Isoflavonen in pflanzlichen Zellsuspensionskulturen / Degradation of Chalcones and Isoflavones in Plant Cell Suspension Cultures

Abstract: Cell suspension culture of Phaseolus aureus, Glycine max and Pisum sativum have been used to determine the extent of chalcone and isoflavone catabolism. The A-rings of calcones and isoflavones with both resorcinol and phloroglucinol pattern of sub­stitution have unequivocally been shown to be degraded as measured by carbon dioxide production The earlier described catabolic pathway of chalcones with the B-ring liberated as a substituted benzoic acid has been verified using another chalcone. With the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

1975
1975
1983
1983

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…Feeding experiments with labeled isoflavones in cell cultures have shown that turnover may be explained by assuming catabolic reactions to occur (8).…”
Section: Izmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding experiments with labeled isoflavones in cell cultures have shown that turnover may be explained by assuming catabolic reactions to occur (8).…”
Section: Izmentioning
confidence: 99%
“…Such demethylation reactions are regarded as initial steps in degradation reactions of N-methylphenylurea herbicides, phenylethylamine alcaloids such as hordenine (see Fig. 9), p-O-methyl benzoic and cinnamic acids (9) or isoflavone aglycones (8).…”
Section: Demethylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ist das Abbauschema von Chalkonen und den ihnen isomeren Flavanonen gezeigt. Durch formale Spaltung zwischen der Carbonylgruppe und dem A-Ring entstehen Zimtsauren, deren weiterer Abbau zu den dem B-Ring entsprechenden Benzoesauren fiihrt (JANISTYN et al, 1971;BERLIN et al, 1974). Durch Venvendung spezifisch Ring-A-markierter Substrate konnten wir zeigen, daB sowohl die Phloroglucinringe wie auch die Resorcinringe einem vollstandigen Abbau unterliegen.…”
Section: Abb 5: Abbauwege Von Flavonolen In Pflanzlichen Zellsuspensunclassified
“…Der Abbau glykosidischer Naturstoffe durch Pflanzen und Mikroorganismen wird oft mit einer Abspaltung der Zuckerreste durch spezifische Glykosidasen eingeleitet (PODSTOLSKI und LEWAK, 1970;HAY et al, 1961). Vor kurzer Zeit wurden auch für die Isoflavone der Kichererbse, für die bereits Umsatz und Abbau festgestellt worden war (BARZ, 1969;BARZ und HOSEL, 1971;BERLIN et al, 1974) HOSEL, in Vorbereitung). Junge Kichererbsenpflanzen enthalten danach in betrachtlicher Menge p-Monoglukosidasen, die spezifisch die Spaltung von'Isoflavon-7-O-B-glukosiden katalysieren.…”
Section: Introductionunclassified